2013
DOI: 10.1590/1516-4446-2012-0905
|View full text |Cite|
|
Sign up to set email alerts
|

Depressive morbidity among elderly individuals who are hospitalized, reside at long-term care facilities, and are under outpatient care in Brazil: a meta-analysis

Abstract: Objectives: i) To investigate studies published between 1991 and 2010 on the prevalence of depressive morbidity (major depressive disorder [MDD], dysthymia and clinically significant depressive symptoms [CSDS]) among elderly Brazilians assisted at healthcare facilities; ii) to establish the prevalence of depression and identify its related factors; and iii) to conduct a metaanalysis to assess the prevalence of depressive syndrome among elderly individuals assisted or hospitalized at healthcare facilities. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
0
9
0
7
Order By: Relevance
“…A se julgar pela capacidade funcional e cognitiva da maioria dos participantes, pode-se compará-los a indivíduos residentes em instituições de longa permanência, entre os quais a prevalência de depressão pode ser ainda mais elevada. Castro-de-Araújo et al 43 , em uma revisão com metanálise de estudos brasileiros, identificaram a ocorrência de sintomas depressivos clinicamente significativos em 65% de idosos institucionalizados, havendo associação entre depressão, sexo feminino, idade e demência. Tendo em vista a já estabelecida relação entre transtorno de humor depressivo e incapacidade 44,45 , a presença de todas essas características contribuem para justificar as taxas elevadas de depressão encontradas nesta pesquisa, assim como sua associação com a sobrecarga dos cuidadores familiares de idosos dependentes, identificada de forma independente em relação aos outros fatores.…”
Section: Discussionunclassified
“…A se julgar pela capacidade funcional e cognitiva da maioria dos participantes, pode-se compará-los a indivíduos residentes em instituições de longa permanência, entre os quais a prevalência de depressão pode ser ainda mais elevada. Castro-de-Araújo et al 43 , em uma revisão com metanálise de estudos brasileiros, identificaram a ocorrência de sintomas depressivos clinicamente significativos em 65% de idosos institucionalizados, havendo associação entre depressão, sexo feminino, idade e demência. Tendo em vista a já estabelecida relação entre transtorno de humor depressivo e incapacidade 44,45 , a presença de todas essas características contribuem para justificar as taxas elevadas de depressão encontradas nesta pesquisa, assim como sua associação com a sobrecarga dos cuidadores familiares de idosos dependentes, identificada de forma independente em relação aos outros fatores.…”
Section: Discussionunclassified
“…Além disso, foram utilizados instrumentos diferentes para mensuração dos sintomas depressivos, fatores que podem ter contribuído para a grande variabilidade na prevalência do transtorno na população estudada. 5 Apesar da alta prevalência de depressão, a doença ainda é bastante subdiagnosticada e não detectada, levando ao não tratamento dos sintomas. Os achados de pesquisa 6 realizada em um hospital universitário brasileiro mostram que, entre os idosos hospitalizados e com sintomas depressivos, apenas 3% tinham registro, em seus prontuários, sobre o diagnóstico psiquiátrico.…”
Section: Introductionunclassified
“…Similar results were found in a study carried out with elderly people enrolled in the Family Health Strategy in which a negative relation between depression and widowhood was identified. The results of both studies are divergent from those found in the literature, since having a partner has been considered a psychosocial protective factor, promoting mutual support and coping with adverse situations (2)(3)(4)(5) .…”
Section: Discussionmentioning
confidence: 57%
“…In this group, depression is one of the most frequent chronic diseases that increases the possibility of developing functional incapacity, increased financial expenses, poor quality of life, and the use of health services, and can lead to the most severe outcome of the disease, i.e. suicide (1)(2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation